2016
DOI: 10.1097/j.pain.0000000000000800
|View full text |Cite
|
Sign up to set email alerts
|

Brief telephone-delivered cognitive behavioral therapy targeted to parents of children with functional abdominal pain: a randomized controlled trial

Abstract: Pediatric functional abdominal pain disorders (FAPD) are associated with increased healthcare utilization, school absences, and poor quality of life (QoL). Cost-effective and accessible interventions are needed. This multi-site study tested the effects of a 3-session cognitive-behavioral intervention delivered to parents, in person or remotely, on the primary outcome of pain severity and secondary outcomes (process measures) of parental solicitousness, pain beliefs, catastrophizing, and child-reported coping. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
65
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(71 citation statements)
references
References 63 publications
0
65
0
3
Order By: Relevance
“…Studies including parents of children who have chronic pain have found that discouraging and solicitous responses are related to negative outcomes, eg, children having higher levels of pain intensity and disability or depression and anxiety . On the other hand, coping responses have been found to be predictive of lower pain intensity and/or disability, as well as an array of somatic symptoms, depression or anxiety . In this study, experienced teachers reported responding to students with chronic pain using with solicitous responses more often than student teachers.…”
Section: Discussionmentioning
confidence: 59%
“…Studies including parents of children who have chronic pain have found that discouraging and solicitous responses are related to negative outcomes, eg, children having higher levels of pain intensity and disability or depression and anxiety . On the other hand, coping responses have been found to be predictive of lower pain intensity and/or disability, as well as an array of somatic symptoms, depression or anxiety . In this study, experienced teachers reported responding to students with chronic pain using with solicitous responses more often than student teachers.…”
Section: Discussionmentioning
confidence: 59%
“…Given that 17% of children in this study experienced stress and anxiety, psychological strategies need to be used in concert with dietary interventions. Randomized and observational studies provide relatively compelling but limited evidence that psychological interventions are associated with improved pain tolerance, reduced anxiety, increased nonpain behavior, and improved self‐management . In a prospective study in which 322 children with functional abdominal pain were followed to young adulthood, the lifetime risk of anxiety and depression were 51 and 40%, respectively (compared 20 and 16%, respectively, in controls) .…”
Section: Discussionmentioning
confidence: 99%
“…These behaviors are driven by threat appraisals or catastrophic thinking about pain and predict both disability and health outcomes. We have previously reported that by intervening only with parents, through reduction of pain threat, and changing parental behaviors, we can improve health outcomes in children with FAPD . Hence, parental behaviors and cognitions are important predictors and treatment targets for children with FAPD.…”
Section: Parent Psychological Factorsmentioning
confidence: 99%